Ensino de literatura : da Paideia ao paradigma sistêmico - Gabrielli, Mariele (My University, 2016)
This dissertation investigates the development of educational thinking, seeking approaches with the science’s paradigmatic ruptures, to verify how these processes intersect in teaching Literature. The research is based in the bibliographic exploration. The paradigms of science and its implications in the educational process are based in theoretical frameworks from Aranha (2006), Behrens (1999), Bertalanffy (1973), Capra (1996), Moraes (2002), Morin (2000, 2002, 2004) and Santos (1988). About the teaching of Literature the theoretical support is based in Candido (2011), Coelho (1980, 2000), Cosson (2006), Pinto (2014), Zilberman (1990, 2005) and Zinani and Santos (2002, 2004). The theoretical immersion, on one hand, shows that the Literature teaching centered in chronological base of literary periods, the use of text for transmission of values or the language of grammar teaching, it relates to the design of science arising from the traditional, dominant paradigm. On the other hand, reading practices that conceive literariness of texts, the significations from de students’ experiences and the conditions offered by the mediator teacher, it has the marks of emerging scientific model, the systemic thinking in education. The temporal redemption about the presence of Literature since the beginning of the constitution of the Brazilian nation and the necessary actions for the literary schooling demonstrate how the teaching of Literature is associated with the historical moment lived by the nation and the scientific thinking adopted at the time. The research indicates that the teaching of Literature, by reconnection of knowledge, may be the indicator of the changes that are necessary to the contemporary educational process and Cosson (2006) methodological guidance for the promotion of literary literacy is a possibility of teaching in the systemic perspective. Through the relationships established between the evolution of educational thinking and the science’s paradigmatic ruptures, it is suggested that the teaching of Literature is directed to the reader formation, centered on the humanization process, the significations that the student prepares for his readings and interactions established with reality. The research also provides theoretical support for the teaching of Literature, in High School, according to contemporary assumptions of education and science, from the perspective of literary literacy.
Esta dissertação investiga a evolução do pensamento educacional, buscando aproximações com as rupturas paradigmáticas da ciência, para verificar como esses processos se intercruzam no ensino de Literatura. A pesquisa pauta-se na exploração bibliográfica. Os paradigmas da ciência e suas implicações no processo educativo fundamentam-se em referenciais teóricos de Aranha (2006), Behrens (1999), Bertalanffy (1973), Capra (1996), Moraes (2002), Morin (2000, 2002, 2004) e Santos (1988). No que se refere ao ensino Literatura, busca-se suporte teórico em Candido (2011), Coelho (1980,2000), Cosson (2006), Pinto (2014), Zilberman (1990, 2005) e Zinani e Santos (2002, 2004). A imersão teórica, de um lado, evidencia que o ensino de Literatura centrado no viés cronológico dos períodos literários, no uso do texto para transmissão de valores ou para o ensino da gramática da língua relaciona-se à concepção de ciência advinda do paradigma tradicional, dominante. De outro, práticas leitoras que concebem a literariedade dos textos, a atribuição de sentidos a partir das vivências do estudante e das condições oferecidas pelo professor mediador trazem as marcas do modelo científico emergente, do pensamento sistêmico na educação. O resgate temporal realizado sobre a presença da Literatura desde os primórdios da constituição da pátria brasileira e as ações necessárias para a escolarização do literário demonstram como o ensino de Literatura tem associação com o momento histórico vivido pela nação e com o padrão científico de pensamento adotado na época. A pesquisa sinaliza que o ensino de Literatura, pelo viés da religação dos saberes, pode ser o fio condutor para as mudanças que se fazem necessárias ao processo educativo contemporâneo e a orientação metodológica de Cosson (2006) para a promoção do letramento literário é uma possibilidade de ensino sob a perspectiva sistêmica. Através das relações estabelecidas entre a evolução do pensamento educacional e as rupturas paradigmáticas da ciência sugere-se que o ensino de Literatura seja orientado para a formação do leitor, centrado no processo de humanização, nas significações que o aluno constrói para suas leituras e nas interações estabelecidas com a realidade. A investigação também apresenta subsídios teóricos para o ensino de Literatura, no Ensino Médio, consoante com os pressupostos contemporâneos de educação e de ciência, a partir da perspectiva do letramento literário.
Keywords: Literatura - Estudo e ensino (Ensino médio); Letramento; Educação; Literature - Study and teaching; Literacy; Education